Next-Generation Data Pipeline Designs for Modern Analytics : A Comprehensive Review - Anupkumar Ghogare, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This comprehensive article examines the transformative evolution of data pipeline architectures in modern analytics, focusing on the integration of real-time and batch-processing methodologies to meet contemporary data processing demands. The article investigates how advanced frameworks like Apache Spark and Databricks, coupled with innovative technologies such as Delta Lake, are reshaping traditional data processing paradigms to accommodate increasing data volumes and complexity. Through a detailed article of hybrid pipeline architectures, data quality mechanisms, and observability practices, this paper demonstrates the critical role of next-generation pipeline designs in enabling organizations to build scalable, reliable, and maintainable data infrastructures. The article explores the implementation of ACID-compliant data lake technologies, automated monitoring systems, and sophisticated quality assurance methods that collectively ensure data integrity and processing efficiency. Key findings highlight the significance of emerging technologies, including edge computing and serverless architectures, in shaping future data pipeline designs. The article provides valuable insights into architectural patterns, best practices, and future trends that organizations can leverage to optimize their data processing capabilities and maintain competitive advantage in an increasingly data-driven business landscape.
Keywords: Hybrid Data Pipeline Architecture; Real-time Stream Processing; Data Quality Observability; Delta Lake Technology; Serverless Data Processing